THE EFFECTIVENESS OF ASSESSING THE QUALITY OF LIFE OF OBESE MILITARY PERSONNEL USING THE SF-36 QUESTIONNAIRE - Jamshid Kutliev; Nizom Ermatov (Central Asian Journal of Medicine, 2025)
This study aimed to evaluate the quality of life (QoL) of obese military personnel using the SF-36 questionnaire. A total of 228 participants from diverse military units, including combat, medical, and educational institutions, were assessed across eight health domains. Results revealed significant disparities in QoL scores between obese and non-obese personnel. Combat units exhibited the highest physical (54.3±1.8) and mental (56.2±1.9) health scores, while communication units and educational institutions scored lower. Obese personnel demonstrated notably reduced physical (44.2±1.3) and mental (49.4±1.6) well-being. The findings emphasize the need for targeted health interventions to address obesity-related challenges in military populations.